Exploitantion of spiritual tourism regarding mother goddess worshipping beliefs in socio-economic development in VietNam - Nguyễn, Thị Phương Lan (2021)
Motheer worship has a special place in the system of indigenous folk beliefs in VietNam. It is assciated with the sporiual life of the people and expreasses cultural identily, customs and traditions of the Vietnamese community for many ganerations. "Practices related to the Việt beliefs in the mother Goddesses of three Realms" was recognized by the United Nations Educatinal, Seientific and Cultunal Organization as the Intangible Cultural Heritage of Humanity on December 1,2016.